Letter (copy) : Goods for Spain - Tewson, Vincent
030-0140-001 Secretary's. HVT/FC/EK/1384. Export. ST/HP.1179. 27th June, 1938. Mr. E. Winstanley, Export Department, The Co-operative Wholesale Society Limited, 1, Balloon Street, MANCHESTER, 4. Dear Mr. Winstanley, GOODS FOR SPAIN. Many thanks for your letter of the 25th June, from which I note that the dried cod and soap has been shipped by s.s. "C.W.S. PROGRESS" and that you anticipate that the goods will be in the hands of the consignee towards the end of this month or the beginning of next. Yours sincerely, Assistant Secretary. 292/946/30/140